Dealing with the Daily Emergency Care: A Case among the Waste Pickers in Surabaya - Loetfia Dwi Rahariyani; Nikmatul Fadilah; Yohanes Kambaru Windi; Nursalam Nursalam (International Journal of Public Health Science (IJPHS), 2016)
Waste pickers are those who collect, sort and sell recyclable waste for a living. Waste pickers are vulnerable to various health problems, particularly high risk of occupational health. This study intended to overview the capability of the waste picker to manage the emergency care due to their unsafe working condition. It is a descriptive study involving 48 waste pickers. The study revealed the poor knowledge and practices of the waste pickers in handling their emergency care. Therefore, it exacerbates their health and become riskier to diseases and illness. Improving the knowledge of the waste pickers regarding the emergency care and the provision of health programs accommodating the waste pickers is necessary.